2003
DOI: 10.1093/petrology/egg057
|View full text |Cite
|
Sign up to set email alerts
|

Time-scales of Differentiation from Mafic Parents to Rhyolite in North American Continental Arcs

Abstract: Young rhyolites and associated lavas and magmatic enclaves from the KatmaiEEENovarupta volcanic system (Alaskan Peninsula), and the Crater Lake and Medicine Lake volcanic system (Cascades) were analyzed for U and Th isotope abundances, as well as major and trace element concentrations, to investigate the timescales of the processes that lead to rhyolite generation in continental arcs. Basalts and basaltic andesites typically migrate from the mantle to the surface within several thousand years. Variations in (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(43 citation statements)
references
References 89 publications
4
38
1
Order By: Relevance
“…Estimates for differentiation timescales based on U-series disequilibria range from thousands (Lundstrom et al, 2003;Rogers, 2004;Johansen et al, 2005) to tens of thousands (Widom et al, 1992;Lowenstern et al, 2006) to hundreds of thousands of years (Allegre and Condomines, 1976;Bourdon et al, 1994;Reagan et al, 2003) and are within the analytical uncertainties of the dates obtained in this study. Our precision is limited by the age of the rocks and we are not able to constrain fractionation timescales to durations shorter than 10 5 years.…”
Section: Timescales Of Magmatic Fractionationsupporting
confidence: 61%
“…Estimates for differentiation timescales based on U-series disequilibria range from thousands (Lundstrom et al, 2003;Rogers, 2004;Johansen et al, 2005) to tens of thousands (Widom et al, 1992;Lowenstern et al, 2006) to hundreds of thousands of years (Allegre and Condomines, 1976;Bourdon et al, 1994;Reagan et al, 2003) and are within the analytical uncertainties of the dates obtained in this study. Our precision is limited by the age of the rocks and we are not able to constrain fractionation timescales to durations shorter than 10 5 years.…”
Section: Timescales Of Magmatic Fractionationsupporting
confidence: 61%
“…Although an individual oscillatory band may represent only short term and very local fluctuations due to feedback mechanisms resulting in local disequilibrium at the crystal/melt interface (e.g., Hoskin, 2000;Fowler et al, 2001;Putnis et al, 1992), in our view an entire oscillatory zone reflects more closely the mean composition of host melt during growth. SiO2 for twelve volcanic sequences that include highly silicic rocks (Anderson, et al, 2000;Bachl, 1997;Briggs, et al, 1993;Heumann and Davies, 1997;Johnson and Grunder, 2000;Mahood, 1981;Metz and Mahood 1991;Reagan, et al, 2003;Stix, et al, 1988;Stix and Gorton, 1990;White and Urbanczyk, 2001) and plutonic data from the Sweetwater Wash pluton, CA (Wark and Miller, 1993), the Searchlight pluton, NV, the Aztec Wash pluton, NV and the Stepninsk pluton, Russia. Note similarly sharp drop in Zr/Hf at ~73 wt% SiO2.…”
Section: Methodsmentioning
confidence: 99%
“…However, Pb isotope data from these volcanoes require that the volcanoes have heterogeneous sources or that crustal assimilation and/or magma mixing occurred during the generation of Bezymianny magmas, mostly in the deeper parts of the system, in order to account for the isotopic contrast between the two volcanic systems. Such assimilation/mixing processes would not significantly alter major and trace element compositions in a manner distinguishable from crystallization of magma during ascent (e.g., Taylor 1980;Reagan et al 2003), but are uniquely observed in Pb isotope compositions. We develop the hypothesis that deep crustal assimilation and/or magma mixing affects Bezymianny magmas.…”
Section: Discussionmentioning
confidence: 99%
“…However, Kamchatka represents a class of arcs within which lower-crustal AFC processes, though they may be pervasive, are not geochemically obvious. In young, thin arcs with MORB-like isotopic compositions, lower-crustal AFC is typically cryptic (Reagan et al 2003) or may go unobserved altogether. High-precision Pb isotope data from the Kamchatka arc suggest that in such arc settings, deep assimilation and magma mixing are important processes in the generation of erupted magmas.…”
Section: Discussionmentioning
confidence: 99%